(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article presents a theoretical analysis of the cross-cultural psychological characteristics of personal autonomy in adolescence, as well as the main factors influencing its formation and development. The study examines adolescents’ perceptions of personal autonomy across different cultural contexts and their interrelations with social values, family relationships, and the educational environment. Personal autonomy is interpreted as an adolescent’s capacity for independent decision-making, regulation of their own behavior, and the ability to act freely within social norms. Particular attention is given to the differential impact of cultural factors on the development of autonomy, as well as the psychological differences observed in individualistic and collectivistic cultural settings. The results of the theoretical analysis substantiate the importance of a cross-cultural approach in studying the formation of personal autonomy in adolescents.